9, 10‐Phenanthrenedione‐Catalyzed, Visible‐Light‐Promoted Radical Intramolecular Cyclization of N‐Biarylglycine Esters: One‐Pot synthesis of Phenanthridine‐6‐Carboxylates. Issue 42 (12th November 2021) - Natarajan, Palani; Chuskit, Deachen; Priya,; Manjeet,
Abstract: A visible‐light photoredox cyclization of a series of N‐biarylglycine esters to phenanthridine‐6‐carboxylates using 9, 10‐phenanthrenedione (PQ) as a catalyst, white LEDs (7 W) as irradiation source and oxygen from air as a terminal oxidant is described. Also, for the reaction, a feasible mechanism is proposed. The N‐biarylglycine esters are converted into radical intermediates by the action of an excited‐state catalyst (PQ*), which are subsequently subjected to intramolecular cyclization followed by dehydrogenation reactions in one‐pot to afford desired products in high yield. Use of inexpensive catalyst, short reaction time and in situ generation of N‐biarylglycine esters are some of the important advantages of present methodology while compared to rose bengal‐photocatalysted protocol already reported by us. Abstract : Using 9, 10‐phenanthrenedione as a catalyst, white LEDs as an irradiation source, and oxygen from air as a terminal oxidant, a visible‐light photoredox cyclization of a series of N‐biarylglycine esters to phenanthridine‐6‐carboxylates is described. When compared to the rose bengal‐photocatalysted approach previously reported by us, the present methodology has several significant advantages, including the use of a low‐cost catalyst, in situ synthesis of N‐biarylglycine esters and overall yields are higher for substrates with electron withdrawing groups on aromatic rings.